A Darwinian Perspective on "Exchange Rate Undervaluation" - Qingyuan Du; Shang-jin Wei (Asian Development Bank (ADB), 2015)
This paper studies how status competition for marriage partners can generate surprising effects on the real exchange rate (RER). In theory, a rise in the sex ratio (increasing relative surplus of men) can generate a decline in the RER. The effect can be quantitatively large if the biological desire for a marriage partner is strong. We also provide within-the People's Republic of China and cross-country empirical evidence to support the theory. As an application, our cross-country estimation suggests that sex ratio as well as other factors in the existing literature can account for the recent evolution in Chinese RER almost completely.
hdl:11540/5200
Keywords: F3; F4; J1; J7; 330; currency manipulation; equilibrium real exchange rate; surplus men